A Pilot Randomised Trial Investigating the Effects of Including Efficacy Messaging on Tobacco Warning Labels. Issue 4 (4th October 2022) - Brinken, Lillian; Ferguson, Stuart G; Buscot, Marie-Jeanne; Schüz, Benjamin; Maynard, Olivia; Schüz, Natalie
Abstract: Introduction: Smokers can respond defensively to health risk communication such as on-pack warning labels, potentially reducing their effectiveness. Theory suggests that risk perception together with self-efficacy reduces defensive responses and predicts target behaviors. Currently, tobacco warning labels globally predominantly target risk and do not explicitly consider efficacy. Aims: This study explores the effectiveness of combining Australian tobacco warning labels with efficacy content to increase quitting intentions. Methods: RCT in 83 smokers over 3 weeks. After a seven-day baseline phase (smoking from usual tobacco packaging), participants were randomized to one of two adhesive labels groups for the remaining 14 days: Standard health warning labels (HWLs) featuring enhanced efficacy messages (experimental group) or unmodified standard HWLs (control group). Participants attached these labels to their tobacco packaging and recorded their cognitions and smoking behavior once daily using Smartphones. Multilevel structural equation modeling was used to test theorized effects of the labels on self-efficacy, risk perception, and intentions to quit. Results: There was no effect of exposure to efficacy messages on either self-efficacy, risk perceptions, or intentions to quit. However, self-efficacy and risk perceptions were positively associated with quitting intentions at the within-person level. Conclusions: The predictive relationships between self-efficacy, risk perception, and intention to quit were supported, however, supplementing standard warning labels with efficacy messages had no effect on these cognitions. Whether this is due to conditioned avoidance of HWLS, characteristics of the messages, or limitations imposed by format are unclear. Implications: Self-efficacy and risk perception predict intentions to quit smoking. Adding efficacy content to tobacco health warnings may have the potential to bolster these cognitions but more research is required to determine the contexts in which this would be effective and who would be likely to benefit. The time course by which exposure to efficacy content might influence cessation self-efficacy and downstream quitting intentions also needs to be investigated.